2018
DOI: 10.1177/0144598718784032
|View full text |Cite
|
Sign up to set email alerts
|

Does change of industrial structure affect energy consumption structure: A study based on the perspective of energy grade calculation

Abstract: In this article, the grades of different kinds of energy sources are distinguished. Thus, we put forward an equivalent electric calculation method, which is compliant with the calculation of various energy resources that have different grades. Based on this aspect, we empirically analyzed the influence of industrial structure changing on energy consumption structure by analyzing panel data in 30 provinces of China from 2003 to 2013. Results showed that the calculated results of equivalent electric calculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The funding gap in R&D investment and the lack of technological innovation capacity have become major bottlenecks in the development of clean energy and new energy industries (Sheng et al, 2021;Pan and Dong, 2022), mainly in renewable hydrogen production and energy storage technologies, wind or tidal energy generation technologies. Notably, as indicated by Model 6, when industrial structure optimization was introduced, the absolute value of the regression coefficients of the core explanatory variables significantly decreased, thereby resonating with Hong et al (2018) findings. In particular, the authors have previously reported that the transformation of the current energy structure depends on the upgrading of the industrial structure.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The funding gap in R&D investment and the lack of technological innovation capacity have become major bottlenecks in the development of clean energy and new energy industries (Sheng et al, 2021;Pan and Dong, 2022), mainly in renewable hydrogen production and energy storage technologies, wind or tidal energy generation technologies. Notably, as indicated by Model 6, when industrial structure optimization was introduced, the absolute value of the regression coefficients of the core explanatory variables significantly decreased, thereby resonating with Hong et al (2018) findings. In particular, the authors have previously reported that the transformation of the current energy structure depends on the upgrading of the industrial structure.…”
supporting
confidence: 67%
“…Fan et al (2023) pointed out that industrial structure upgrading has a significant positive effect on energy structure optimization, and there is a transmission path of "industrial structure upgrading-energy structure optimization-carbon emission reduction. " When the industrial structure optimization increases by 1%, the consumption proportion of the new energy increases by 0.0434% (Hong et al, 2018). Hence, China should use green financial policies to increase clean energy consumption by promoting industrial structure optimization, which can transform the dual structural effects represented by industrial and energy structures to achieve pollution reduction.…”
mentioning
confidence: 99%
“…44 Moreover, the greater the proportion of the tertiary sector is, the greater the proportion of clean energy consumption will be. 45 Therefore, industrial structure upgrading, in which the secondary sector unceasingly declines and the tertiary sector rises, results in a decline in energy consumption to a certain degree. This case reflects that IFTs inhibit the UIS and indirectly increases energy consumption.…”
Section: Hypothesesmentioning
confidence: 99%
“…Industrial upgrading is a process of continuous development and change based on technological progress. From the perspective of supply, technological advancement promotes industrial upgrading by creating new industries, providing new products, changing factor supply ratios, promoting industrial integration, and improving the quality of human capital, thereby promoting industrial upgrading and thus continuing to increase productivity [16]. e technological structure upgrade and the industrial structure upgrade show a one-to-one correspondence in a relatively long period of time.…”
Section: Promotion Mechanism Of Technological Progress Onmentioning
confidence: 99%